Money, Mobile Money and Rituals in Western Kenya: The Contingency Fund and the Thirteenth Cow. (30th April 2018) - Kusimba, Sibel
Abstract: This article, based on fieldwork in Western Kenya from 2012 to 2016, describes how life cycle rituals collect and distribute different forms of money, including land, property, personhood, animals, cash, and digital moneys. It specifically examines a ritual coming of age for adolescent boys. By organizing multiple forms of money relative to the phases of a human life, the past, and the future, these rituals serve to manage and transfer wealth across generations and to give these transfers social and moral dimensions. The study provokes a critique of financial initiatives in the Global South that often assume that the financial goals of the poor are short-term. Résumé: Basé sur des recherches de terrain dans l'ouest du Kenya de 2012 à 2016, cet article décrit comment des rites du cycle de vie sont mobilisés pour collecter et distribuer différentes formes d'objets de valeur, y compris la terre, la propriété, la personnalité, les animaux, l'argent comptant et l'argent numérique. Spécifiquement, nous examinons un rite de puberté pour des adolescents. En organisant plusieurs formes d'argent relatives aux phases d'une vie humaine, le passé et le futur, ces rites aident à gérer et transférer la richesse à travers les générations et donnent à ces transferts des dimensions sociales et morales. L'étude amène vers une critique des nouvelles initiatives financières introduites dans les pays du Sud qui souvent estiment que les objectifs des pauvres ne sont qu'à court terme.